2010
DOI: 10.19173/irrodl.v11i3.842
|View full text |Cite
|
Sign up to set email alerts
|

Development of interactive and reflective learning among Malaysian online distant learners: An ESL instructor’s experience

Abstract: Technology has brought tremendous advancements in online education, spurring transformations in online pedagogical practices. Online learning in the past was passive, using the traditional teacher-centred approach. However, with the tools available today, it can be active, collaborative, and meaningful. A well-developed task can impel learners to observe, to reflect, to strategize, and to plan their own learning. This paper describes an English as a Second Language (ESL) instructor’s attempt to foster inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 27 publications
(20 reference statements)
1
26
0
Order By: Relevance
“…However, researchers around this time are fascinated by the enormous opportunities that the new information and communication technologies afford for collaborative online learning and teaching (micro-level). There are several publications in IRRODL that seek to understand how online collaborative learning occurs and how students are best supported to facilitate their learning processes: Barnard-Brak, Paton, and Lan (2010) developed a typology of self-regulated learning profiles in the online learning environment and several studies deal with the role and function of online tutors (e.g., Ng, 2007;Murugaiah & Thang, 2010). The concept of support is connected with access.…”
Section: Content Analysis: Research Areas and Trendsmentioning
confidence: 99%
“…However, researchers around this time are fascinated by the enormous opportunities that the new information and communication technologies afford for collaborative online learning and teaching (micro-level). There are several publications in IRRODL that seek to understand how online collaborative learning occurs and how students are best supported to facilitate their learning processes: Barnard-Brak, Paton, and Lan (2010) developed a typology of self-regulated learning profiles in the online learning environment and several studies deal with the role and function of online tutors (e.g., Ng, 2007;Murugaiah & Thang, 2010). The concept of support is connected with access.…”
Section: Content Analysis: Research Areas and Trendsmentioning
confidence: 99%
“…Recently, Murugaiah and Thang (2010) utilized an active, collaborative, asynchronous approach to teaching English as a second language online to students at the National University of Malaysia. They incorporated interactive and reflective writing activities which helped to raise students' awareness of their own learning processes and to become actively engaged learners responsible for their own learning.…”
Section: Introductionmentioning
confidence: 99%
“…The tutor's involvement through prompt response and feedback to queries by learners encouraged them to participate to a greater extent in the OLF and this finding is widely echoed in the literature (Pramela 2011;Puvaneswari & Thang 2010;Dennen 2005;Salmon 2004). The distance learners in the present study seemed to find it crucial to obtain their tutor's validation to information and answers.…”
Section: Tutormentioning
confidence: 84%
“…As a result, even though the potential for active group participation and group interaction exists, learner participation in the OLF does not always take place (Kreijns et al 2003;Harasim 1989). This situation has prompted researchers to study factors influencing participation in the OLF and numerous factors have been recorded, for instance, role of the facilitator (Pramela 2011;Puvaneswari & Thang 2010;Dennen 2005;Salmon 2004;Tsang et al 2002); design of discussion activities (Vonderwell & Zachariah 2005;Aspden & Holm 2004;Lamy & Hassan 2003); learner characteristics (Gerbic 2006;Tsang et al 2002) and assessment grades (Supyan Hussin 2008;Gerbic 2006). The findings of these studies have shown that it is important to consider the needs and perceptions of learners in order to understand their participation in the OLF.…”
Section: Participation In An Online Forummentioning
confidence: 99%